EKONOMI ISLAM DAN RASIONALITAS - Maryam Batubara; Putri Filza Salsabila Surbakti; Febri Andriawan Purba; Indah Purnama Sari; Yeprian Aji Ratukarangga (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2023)
Islamic economics is not only a set of economic practices carried out by Muslim individuals and groups, but also a set of economic behaviors based on Islamic teachings. The concept of rationality in economics is intrinsically linked to the economic system. The view of the concept of rationality influences how people act with respect to their economic actions and life goals. Mastering Islamic economics and rationality is the aim of this study. A search in the library was used in this study. According to the results of research on economic rationality, people act in a reasonable (rational) way and avoid making decisions that worsen their situation. There are two types of rationalism: rationality of self-interest and rationalization of current intentions.